Investors’ Perception towards Mutual Fund - Sushmita Malla (Journal of Corporate Finance Management and Banking System, 2024)
The purpose of the study is to identify the investors’ perception toward mutual fund. The study considered Investors’ perception toward mutual fund as the dependent variable and Fund scheme, Risk & Return, Level of investors’ knowledge as dependent variable. Data for the study was collected through structured questionnaires method by using five point Likert scale. A total of 72 investors are participated in this study. This study examine the impact of Fund scheme, Risk & Return, Level of investors’ knowledge on investors’ perception. Researcher used questionnaires as a research instrument for the data collection which was analyzed using SPPS software using the tool descriptive statistics, correlation and regression. Correlation and regression analysis were used to find out the relationships and state the impact between the variable. Analyzed result revealed the investor’s level of knowledge variable has positive significant impact on Investors’ Perception in mutual fund whereas fund scheme and Risk & Return has insignificant impact on Investors’ Perception in mutual fund.